Program Karang Taruna dalam Pengembangan Nutripreneur Masa Depan - Wahyuningtyas, Widayani; Riadhasilmi, Nazzala; Rezky, Nur Sofia; Butar, Yelvi Firstiana Butar (Abdimas Indonesian Journal, 2024)
In the year 2045, Indonesia has an ambitious vision to become the "Golden Indonesia," with one of the key success factors being human development and the mastery of science and technology. In the current economic development of Indonesia, the youth unemployment rate remains high, posing significant social problems if not addressed seriously. One solution is to foster a spirit of social entrepreneurship in every individual in society, especially the youth who are the backbone of the nation. Therefore, community service activities through this entrepreneurship seminar will be conducted in Karang Taruna RW 07 Tomang, West Jakarta, scheduled for November 4, 2023, as our participation as students in building Indonesia towards the Golden Generation.The objective of community service (PKM) is to cultivate the entrepreneurial spirit among the youth of Karang Taruna and raise awareness of the importance of selling healthy food. In the outreach activities, the attendance level of Karang Taruna members in the seminar is 15 individuals (16-20 years old), with data collected through a closed questionnaire via Google Form. The results obtained indicate that the partners feel assisted by the implementation of this program because it helps the youth build an entrepreneurial spirit, create job opportunities for themselves and others, and contribute to the local economy.